Iz gledališke zgodovine - Smolej, Tone (Clotho, 2024)
This article presents a fragment of Slovene theatre history, focusing on performances on the stage of the German-language Theatre of the Carniolan Provincial Estates (Ständisches Theater) in Ljubljana during its 1833/34 season. The introductory part describes Amalie Maschek, an opera singer with extensive experience in theatre practice, who was then directing the Ljubljana stage, followed by a detailed description of the season’s repertoire. The focus is exclusively on the dramatic pro-ductions, and not on the opera performances. The article shows that the theatre’s repertoire, which included romantic rescue plays, classic comedies, vaudeville comedies (comédie-vaudeville), and magical fairy tales, was not far behind the Viennese and even Parisian productions of the first half of the nineteenth century and that the audience in Ljubljana could often see the plays just a few years after their premiere.
Keywords: 1833/34 theatre season; gledališka sezona 1833/34; Maschek, Amalie; Stanovsko gledališče v Ljubljani; Theatre of the Carniolan Provincial Estates